On the nature of Dennett’s narrative “self” - León, Malena (Griot : Revista de Filosofia, 2021)
Dennett's theory of personal identity argues that the “self” is no more than a center of narrative gravity. One of the main hurdles to assessing this proposal lies in the fact that it is difficult to understand what the nature of Dennett's concept of "self" is; specifically, what are the ontological and epistemological commitments that can be attributed to the phenomenon in question. In this article we claim that the best way to make an interpretative reconstruction of his notion of "self" is appealing to the distinction elaborated by Reichenbach between three classes of entities, Concreta, Abstracta, and Illata, and understanding the narrative centers of gravity as a case of Reichenbachian Abstracta. We defend that understanding the narrative centers of gravity as Abstracta in the sense of Reichenbach is pertinent and illuminating given that: i) although he does not apply it directly to the problem of the nature of the "self", Dennett does use Reichenbach's distinction in other parts of his work; ii) Dennett explicitly draws an analogy of the "self" with the centers of gravity that are, precisely, one of his examples of Abstracta; iii) this way of understanding the "self" allows us to give sense and better understand certain aspects of Dennett’s narrative theory. Besides allowing us to clarify the metaphors used by Dennett in the elaboration of his narrative theory, such conceptual elucidation allows us to better understand the distinction between the three classes of intentional psychology drawn by Dennett (1987) and is useful in suggesting to which of these three types the concept of "self" belongs.